Hunan Valin & Arcelormittal in partnership : dancing with dragons - Williamson, Peter J.; Sharma, Sanjay; Xu, Sitao ([London] : SAGE, 2016)
This case explores how the Chinese company, Hunan Valin Steel, used overseas acquisitions and a partnership with the world's largest steel producer, Arcelor Mittal, to improve competitiveness and strategically re-position itself in the context of consolidation in the Chinese steel industry.
Originally Published in: Williamson, P., Sharma, S., & Sitao, X. (2011). Hunan Valin & ArcelorMittal in Partnership: Dancing with dragons. Cambridge: University of Cambridge, Judge Business School.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Hunan Valin Steel (Firm); ArcelorMittal (Firm); Competition -- Case studies; Strategic alliances (Business) -- Case studies; Consolidation and merger of corporations -- Case studies